2019
DOI: 10.1177/1753425919866006
|View full text |Cite
|
Sign up to set email alerts
|

Innate immunity of surfactant protein A in experimental otitis media

Abstract: Surfactant protein A (SP-A) plays an important role in innate immune response and host defense against various microorganisms through opsonization and complement activation. To investigate the role of SP-A in non-typeable Haemophilus influenzae (NTHi)-induced acute otitis media, this study used wild type C57BL/6 (WT) and SP-A knockout (KO) mice. We divided mice into an infection group in which the middle ear (ME) was injected with NTHi and a control group that received the same treatment using normal saline. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
1
10
0
1
Order By: Relevance
“…In the present study, we have found that SP-D is expressed in the mouse ME and ET mucosa, which confirms the previous observation of other studies that found SP-D expressed in porcine ET epithelium [32, 41]. Furthermore, we found that the lack of SP-D could lead to an increase in the inflammatory response to NTHi-induced ME infection and to delay OM resolution as compared to WT mice.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, we have found that SP-D is expressed in the mouse ME and ET mucosa, which confirms the previous observation of other studies that found SP-D expressed in porcine ET epithelium [32, 41]. Furthermore, we found that the lack of SP-D could lead to an increase in the inflammatory response to NTHi-induced ME infection and to delay OM resolution as compared to WT mice.…”
Section: Discussionsupporting
confidence: 92%
“…SP-A and SP-D belong to C-type lectins, which function as PRRs and are important in host defense and regulation of inflammation in the lung. Few studies, including our recent SP-A study [32] on the immune response to OM, exist. To the best of our knowledge, no research was carried out for the role of SP-D in OM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in terms of the significant changes in protein levels, more significant changes were observed in WT infected compared to KO infected. In an otitis media model of infection with non-typeable Haemophilus influenzae, SP-A was shown to modulate the expression of pro-inflammatory markers, IL-6 and IL-1β, and these peaked at higher levels in SP-A KO mice (17).…”
Section: Bacterial Pathogensmentioning
confidence: 96%
“…For example, PRR activation of the NFkB transcription factor cascade by NTHi increased surfactant protein A (SP-A) expression in SP-A knockout mice, causing more severe inflammation. In contrast, wild-type mice showed improved bacterial aggregation, killing and macrophage clearance of the middle ear due to SP-A modulation of the host inflammatory response (Abdel-Razek et al, 2019). Thus, differences in host PRR expression and subsequent signalling pathway activation can lead to differences in how the innate immune response is regulated and how OM disease progresses.…”
Section: Pathogen Recognition and Activation Of Signalling Pathways Within The Innate Immune Responsementioning
confidence: 99%